Social And Economic Phenomena In Shape Behavior And Economic Results - Thamrin Pawalluri (International Journal of Education, Vocational and Social Science, 2023)
ABSTRACT The relationship between social and economic phenomena in shaping economic behavior and outcomes is very complex and can give rise to various problems and challenges.. The purpose of this research is to know how can Social and Economic Phenomena shape economic behavior and results. The research method used in this study is a descriptive qualitative research method. The approach used in this study is a phenomenological approach. The types and sources of data used are secondary data, namely data obtained from literature such as those related to the issues discussed which come from books, journals, news, websites, and archives related to research objectives.The result of this research are social and economic phenomena play an important role in shaping economic behavior and outcomes. Economic sociology has emphasized the importance of understanding the social and cultural factors that influence economic behavior, institutions and organizations. From the results of the study it was found that there are several factors that will shape the behavior and economic results of the current social and economic phenomena, namely: first: factors of social norms and values, second: factors of social networks and capital, third: factors of institutions and rules, fourth: culture and identity, and fifth: power and inequality factors. Keywords: Social and economic phenomena, shape behavior, economic result.